The log from the Sea of Cortez - Steinbeck, John, 1902-1968.; Ricketts, Edward Flanders, 1896-1948.; Steinbeck, John, 1902-1968. (New York : Penguin, 1995)
Joint record of the expedition undertaken in 1940 by author John Steinbeck and marine biologist Edward F. Ricketts, who voyaged 4,000 miles on a sardine boat from California into the Sea of Cortez. Includes a critical introduction and Steinbeck's profile of Ricketts.
"Appendix: About Ed Ricketts": p. 225-274.
"The narrative portion of the book, Sea of Cortez (1941), by John Steinbeck and E.F. Ricketts.".
Originally published: New York : Viking, 1951.
Includes bibliographical references (p. xxv-xxvi) and index.
Adult
Keywords: Ricketts, Edward Flanders, -- 1896-1948 -- Travel -- Mexico -- California, Gulf of; Steinbeck, John, -- 1902-1968 -- Travel -- Mexico -- California, Gulf of; Ricketts, Edward Flanders, -- 1896-1948 -- Voyages and travels; Steinbeck, John, -- 1902-1968 -- Voyages and travels; Marine invertebrates -- Mexico -- California, Gulf of; Marine animals; California, Gulf of (Mexico) -- Description and travel; California, Gulf of (Mexico) -- Description and travel